Magnetic iron oxide nanoparticles for drug delivery: applications and characteristics. (2nd January 2019) - Vangijzegem, Thomas; Stanicki, Dimitri; Laurent, Sophie
ABSTRACT: Introduction : For many years, the controlled delivery of therapeutic compounds has been a matter of great interest in the field of nanomedicine. Among the wide amount of drug nanocarriers, magnetic iron oxide nanoparticles (IONs) stand out from the crowd and constitute robust nanoplatforms since they can achieve high drug loading as well as targeting abilities stemming from their remarkable properties (magnetic and biological properties). These applications require precise design of the nanoparticles regarding several parameters which must be considered together in order to attain highest therapeutic efficacy. Areas covered : This short review presents recent developments in the field of cancer targeted drug delivery using magnetic nanocarriers as drug delivery systems. Expert opinion : The design of nanocarriers enabling efficient delivery of therapeutic compounds toward targeted locations is one of the major area of research in the targeted drug delivery field. By precisely shaping the structural properties of the iron oxide nanoparticles, drugs loaded onto the nanoparticles can be efficiently guided and selectively delivered toward targeted locations. With these goals in mind, special attention should be given to the pharmacokinetics and in vivo behavior of the developed nanocarriers.